Pretreatment of oil palm biomass with ionic liquids: A new approach for fabrication of green composite board - Mahmood, H. (Elsevier Ltd, 2016)
The use of lignocellulosic biomass-based composite materials over petro-materials has received increased attention due to growing environmental awareness, concerns for environmental sustainability, an increasing global waste problem and depletion of fossil fuels. Effective pretreatment of lignocellulosic biomass is an important and challenging task for production of engineered composite panels. In the present work, the effect of ionic liquids (ILs) pretreatment on the properties of thermo-molded biocomposite board fabricated from oil palm frond (OPF) lignocellulosic residue and thermoplastic starch (TPS) binder was studied. OPF fiber was pretreated with ILs bmimCl (1-butyl-3-methylimidazolium chloride) and emimdep (1-ethyl-3-methylimidazolium diethyl phosphate). Mechanical, thermal and morphological properties of the biocomposite board prepared from untreated and ILs -treated OPF fibers were investigated. Moreover, lignocellulosic characterization, Fourier transform infrared spectroscopy (FTIR) and thermogravimetric analysis (TGA) were performed to understand the effect of IL pretreatment on OPF fiber. It was noted that thermal stability of the biocomposite board was improved as a result of IL pretreatment. Flexural testing evidenced that biocomposite board fabricated from IL-treated fiber exhibited superior strength and modulus compared to that of untreated composite board. The study clearly indicates that IL-assisted pretreatment could be a highly promising and green technology for effective utilization of lignocellulosic biomass in the biocomposite field. Â© 2016 Elsevier Ltd.